Movement Ecology - Giuggioli, Luca; Nathan, Ran; Giuggioli, Luca; Nathan, Ran
Movement Ecology is an open-access interdisciplinary journal publishing novel insights from empirical and theoretical approaches into the ecology of movement of the whole organism – either animals, plants or microorganisms – as the central theme. We welcome manuscripts on any taxa and any movement phenomena (e.g. foraging, dispersal and seasonal migration) addressing important research questions on the patterns, mechanisms, causes and consequences of organismal movement. Manuscripts will be rigorously peer-reviewed to ensure novelty and high quality.